An investigation into socio economic effects caused by the closure of companies: a case study of ZISCOSTEEL. - Singagwari, Clarridge (Midlands State University, 2019)
This study‟s main focus area was to investigate the socio- economic effects of company closures. This research study is based on the background of numerous company closures across the globe and in Zimbabwe. Data was collected from the workers, company management, social services, nurses, police, councilors and teachers. Interviews and questionnaires were employed in the collection of data. The collected data was examined and interpreted. The study found out the majority of skilled workers moved on and what remains are a semi- skilled and non-skilled workers who failed to move on because of lack of courses. The Company last recruited six years ago, 75% of the workers are in their early forties and fifties and hence find it difficult to find employment elsewhere. The study also found out that the workers were owed sixty months wages, were not given severance packages and are facing challenges in buying food, paying bills, accessing medication, paying school fees. The study revealed 30 % of families broke down while crime and prostitution increased significantly. Social services are overwhelmed as 100% of the workers are in need of assistance. Basing on the findings of the study the researcher concluded that the workers are faced with serious socio economic challenges which they cannot overcome given the current state of affairs .The study recommends that the Government and the Company should consider sourcing funds to pay the workers their severance packages to enable them to start income generating projects .The Government should also consider engaging other stakeholders such as Non-Governmental Organizations to help in the counselling of the workers as well as conducting and funding of vocational courses and self-sustenance projects.